Neonatal Autoimmune Subepidermal IgG/IgA Blistering Disease With Severe Laryngeal and Esophageal Involvement: A Report of a Case and Review of the Literature. (October 2020) - Raiber, Sofia; Sezin, Tanya; Sadik, Christian D.; Bergman, Reuven; Avitan-Hersh, Emily
Abstract : Abstract: Neonatal autoimmune subepidermal blistering disease is rare. Mucosal involvement is more common in neonatal linear immunoglobulin A (IgA) bullous dermatosis. We describe a neonate with subepidermal cutaneous blistering disease with severe laryngeal and esophageal involvement leading to acute respiratory distress. Histopathology demonstrated a subepidermal blister with neutrophils and eosinophils at the dermal base. Collagen IV was detected at the dermal floor, and direct immunofluorescence showed linear IgG, IgA, and C3 deposits at the basement membrane zone. The patient demonstrated markedly increased serum levels of anti-BP180 NC16A and anti-BP230 IgG antibodies (Abs) but failed to show anti-LAD-1 IgA Abs. His healthy mother showed serum anti-LAD-1 IgA Abs but did not show anti-BP180 and anti-BP230 Abs. The neonate responded promptly to systemic corticosteroid therapy. A review of the literature detected 11 cases of neonatal subepidermal blistering disease with linear IgA deposits. Nine of these cases demonstrated coexisting linear IgG deposits, often with C3. Respiratory compromise was present in most of the cases. Neutrophils and eosinophils were commonly present in the inflammatory cell infiltrates. Besides our case, 2 cases of neonatal IgG/IgA subepidermal blistering disease with esophageal involvement were previously described. IgA Abs were present in the sera of both cases. Anti-LAD-1 IgA Abs were detected in the mother's serum of our case alone, but IgA Abs do not cross the placenta. Our case was consistent with neonatal IgG/IgA pemphigoid. Neonatal IgG/IgA subepidermal blistering disease may be associated with severe laryngeal and esophageal involvement leading to respiratory compromise. Expedited diagnosis and prompt treatment are warranted.